Causal approach for the electron-positron scattering in generalized quantum electrodynamics - Bufalo, R. [UNESP]; Pimentel, B. M. [UNESP]; Soto, D. E. [UNESP] (Amer Physical Soc, 2014)
In this paper we study the generalized electrodynamics contribution to the electron-positron scattering process e(-)e(+) -> e(-)e(+), i.e., Bhabha scattering. Within the framework of the standard model and for energies larger than the electron mass, we calculate the cross section for the scattering process. This quantity is usually calculated in the framework of Maxwell electrodynamics and (for phenomenological reasons) is corrected by a cutoff parameter. On the other hand, by considering generalized electrodynamics instead of Maxwell's, we show that the Podolsky mass plays the part of a natural cutoff parameter for this scattering process. Furthermore, by using experimental data on Bhabha scattering we estimate its lower bound. Nevertheless, in order to have a mathematically well-defined description of our study we shall present our discussion in the framework of the Epstein-Glaser causal theory.